Compare styles for encounter to stress, life expectancy and scale of hardness in patients stricken to AIDS and MS - Mahdavi, Abed; Awang, Hamidin; Taghizadeh, Mohammad Ehsan; Isazadeh, Soudabeh; Samkhaniyan, Eshagh; Kamran, Fatemeh (Scholars Research Library, 2015)
The aim of this research is to compare styles encounter to stress, Life Expectancy and scale of hardness in patients Stricken to AIDS and MS. The method is practical- comparative type. The society consists of all patients Stricken to aids and MS who refereed in order to receive specialty treatment to Imam Khomeini Hospital and Sina Hospital in Tehran. From said society, a sample with volume 100 people (50 patients Stricken to AIDS and 50 patients Stricken to MS) were selected by sampling and have been evaluated by Cobasa and Maddi Personal Insight questionnaire and Schneider scale of hope 1991, style encounter with stress of Endler and Parker 1990. Then, data collected have been analyzed by descriptive methods and SPSS software. The results of research showed that there is significant difference between two groups of patients Stricken to AIDS and MS from style of encounter point of view with stress, as if patients Stricken to AIDS use more avoidance styles and patients Stricken to MS use more encounter styles. Also, there was significant difference between two groups from Life Expectancy as if patients Stricken to AIDS use more avoidance style and patients Stricken to MS use more emotional style. Also, there was significant difference from Life Expectancy. In other word, scale of Life Expectancy was more in MS group to AIDS. In addition to, there was difference from hardness point of view. In other word, scale of hardness is more than MS to AIDS.